ANALISIS PERBANDINGAN PERLAKUAN AKUNTANSI TERHADAP ASET BIOLOGIS DAN NON BIOLOGIS (Studi Kasus pada CV. Fatherland Farm Tondano) - Putra, Abram Ventura Wardana; Pangemanan, Sifrid S.; Wokas, Heince R. N. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2016)
The accounting treatment for biological assets in Indonesia does not have mutual standards so, many agribusiness companies reported their biological assets just like the standards that used to report the non-biological assets. Characteristics of different biological assets can cause mistakes in recording if we use the same standards with non-biological assets. This study aimed to comparing the accounting treatment made by the company between two types of assets that owned by the company. The result of this research found that accounting treatment between the two types of asset does not have significant differences. The differences in the accounting treatment of these assets only in the measurement of assets and discontinuation. Companies measure the value of both types of assets in accordance with the acquisition price. But the company did not recognize the depreciation of their biological assets. At the time of biological assets termination, the company immediately reclassified the biological assets to the inventories that available to sale, while for non-biological assets, there are two types of termination that is for resale and stored as damaged goods. Considering to the characteristics of the biological assets, company should establish fair value in the measurement of biological assets. Keywords: Biological Assets, fixed assets.